Integrating Techno-Entrepreneurial Relationship Marketing (TERM) to Strengthen Student Entrepreneurial Competitiveness in Central Java - Widyanti, Dika Vivi; Suroija, Noor; Nahar, M.; Wibowo, Bagus Yunianto; Setiawan, Andi; Wahyuni, Sri; Supaya, Sandi; Riyanto, Makmun (RSF Conference Series: Business, Management and Social Sciences, 2025)
The Techno-Entrepreneurial Relationship Marketing (TERM) model is a strategic framework that integrates digital innovation with relationship-based marketing to support student entrepreneurs in Central Java. This research adopts a mixed-methods design to evaluate how TERM impacts marketing outcomes by focusing on digital adoption, entrepreneurial orientation, and proactive customer interaction. Surveying 150 student-run ventures across 35 regions, the study finds that TERM significantly improves marketing performance by enabling responsive, data-informed strategies and fostering deeper customer relationships. Tools such as CRM systems, social media, and analytics platforms enhance customer retention and market relevance. The study concludes that embedding TERM into entrepreneurship education equips students with the digital and relational competencies needed to compete effectively in the evolving business landscape.